2022
DOI: 10.3390/ijms23094967
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Human Amniotic Fluid Mesenchymal Stem Cells Preserve Microglia and Neuron Cells from Aβ

Abstract: Background: Neuroinflammation is involved in neuronal cell death that occurs in neurodegenerative diseases such as Alzheimer’s disease (AD). Microglia play important roles in regulating the brain amyloid beta (Aβ) levels, so immunomodulatory properties exerted by mesenchymal stem cells may be exploited to treat this pathology. The evidence suggests that the mechanism of action of human amniotic fluid stem cells (hAFSCs) is through their secretome, which includes exosomes (exo). Methods: We examined the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…A study was conducted to investigate the effect of exosomes on the SH‐SY5Y interaction between AD neurons and microglia. The results demonstrated that hAFSC‐Exos could inhibit the inflammatory response, oxidative stress, and microglial apoptosis and could be a potential therapeutic drug for diseases related to inflammation such as AD in the future 195 …”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 91%
See 1 more Smart Citation
“…A study was conducted to investigate the effect of exosomes on the SH‐SY5Y interaction between AD neurons and microglia. The results demonstrated that hAFSC‐Exos could inhibit the inflammatory response, oxidative stress, and microglial apoptosis and could be a potential therapeutic drug for diseases related to inflammation such as AD in the future 195 …”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 91%
“…The results demonstrated that hAFSC-Exos could inhibit the inflammatory response, oxidative stress, and microglial apoptosis and could be a potential therapeutic drug for diseases related to inflammation such as AD in the future. 195 Neuroinflammation is associated with neuronal cell death in AD. Coenzyme Q10 (CoQ10), as a supplement to anti-inflammatory and antioxidant stress, can improve AD-related inflammation and oxidative stress.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Some in vitro and in vivo recent studies demonstrated the applicability of exosomes derived from stem cells (SCs) for therapeutic purposes. The SC-derived exosomes have demonstrated the potential to treat many diseases and disorders including neurodegenerative diseases [ 178 , 179 ], cardiovascular ischemia [ 180 , 181 , 182 ], osteoporosis and osteoarthritis [ 183 , 184 ], and kidney and liver diseases [ 185 , 186 ]. EV-based therapy represents a highly potent cell-free therapy approach.…”
Section: Therapeutic Perspectives—mirnas and Evs From Stem Cellsmentioning
confidence: 99%
“…EVs derive from MSCs and anti-inflammatory immune cells that can reduce the inflammatory damage and cell stress ( Thome et al, 2022 ). The exosomes of human amniotic fluid MSCs can treat the inflammation-related neurological diseases by reducing inflammation caused by microglia and improving neurotoxicity ( Zavatti et al, 2022 ). EV-mediated the delivery of DnaJ Homolog Subfamily B Member 6 (DNAJB6) molecular chaperone inhibits the aggregation of polyQ and HTT proteins to delay the onset of HD ( Joshi et al, 2021 ).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%